COMPARISON OF PAIN EXPERIENCE IN PATIENTS UNDERGOING SUB-TENON'S ANESTHESIA VERSUS PERIBULBAR ANESTHESIA DURING ELECTIVE VITREORETINAL SURGERY. Issue 10 (October 2022) - Ripa, Matteo; Schipa, Chiara; Kopsacheilis, Nikolaos; Nomikarios, Mikes; De Rosa, Carlo; De Rosa, Pasquale; Motta, Lorenzo
Abstract : Over the years, vitreoretinal surgery has been performed under different forms of anesthesia. Both sub-Tenon's injection and peribulbar block are most widely used in ocular posterior segment surgery. Despite their common use, patients' pain and discomfort after these procedures are still challenging. Abstract : Purpose: To assess and compare the patients' discomfort and pain experienced during anesthesia, pars plana vitrectomy, and 24 hours postoperatively after sub-Tenon's injection (STI) versus peribulbar block (PB) in elective vitreoretinal surgery. Methods: Retrospective study involving 80 patients who underwent elective vitreoretinal surgery receiving either PB (Group 1, n = 40) or STI (Group 2, n= 40) between January 2021 and March 2022. Patients' pain experienced during the procedure and 24 hours postoperatively were assessed using a pain scale and a two-section questionnaire. One hour postoperatively, patients were asked to rate the level of pain they felt during the entire procedure by pointing at a 0 to 100 Visual Analog Scale. Subsequently, patients answered a two-section questionnaire regarding pain and discomfort felt 24 hours postoperatively. Results: According to Visual Analog Scale measurements, patients experienced significantly more pain during PB than during STI 1 hour after surgery. Patients undergoing PB experienced more pain than those who underwent STI, experiencing burning and discharge feeling. Patients undergoing STI had a lower pain level score 24 hours postoperatively despite similar discomfort. Conclusion: Sub-Tenon's injection has a lower pain score than PB during the procedure and 24 hours postoperatively, representing a valuable procedure to deliver analgesia in vitreoretinal surgery.